2023
DOI: 10.29128/geomatik.1147639
|View full text |Cite
|
Sign up to set email alerts
|

Yersel lazer tarama yöntemi ve ortofotoların kullanımı ile kültür varlıklarının cephelerindeki malzeme bozulmalarının dokümantasyonu: Mardin Mungan Konağı örneği

Abstract: Yapılarda meydana gelen malzeme bozulmalarına etki eden faktörlerin ve süreçlerin doğru bir şekilde belirlenmesi ve anlaşılması, uygun koruma müdahalelerinin uygulanması ve yapılarda meydana gelecek bozulmalara önlem alınması açısından büyük önem taşımaktadır. Çalışmaya konu olan ve yöreye özgü geleneksel konutların özelliklerini yansıtan tarihi taş bir yapı olan Mardin Mungan Konağı; topografya, malzeme gibi bölgesel unsurların belirleyiciliği altında oluşmuş bir yapıdır. Çalışmanın amacı Mardin ilinde gelene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…In recent years, the use of aerial photography and terrestrial laser scanning has increased significantly in documenting cultural heritage sites and archaeological areas [22][23][24][25][26][27].…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the use of aerial photography and terrestrial laser scanning has increased significantly in documenting cultural heritage sites and archaeological areas [22][23][24][25][26][27].…”
Section: Methodsmentioning
confidence: 99%
“…In light of the data obtained, it was observed that the maximum sunshine duration was in July (12.4 hours) and the minimum in December (4.4 hours). Due to the climatic characteristics of Mardin, stone deterioration is common [31,32].…”
Section: Study Areamentioning
confidence: 99%